1999
DOI: 10.1002/(sici)1096-8628(19990716)85:2<147::aid-ajmg9>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Andersen syndrome autosomal dominant in three generations

Abstract: Andersen syndrome is a rare entity and comprises potassium sensitive periodic paralysis, ventricular arrhythmia, and an unusual facial appearance; syncope and sudden death have also been reported. The recognition of the characteristic face permits an early diagnosis in order to detect the severe systemic manifestations that are associated with this syndrome. The genetic defect is not linked to any other form of potassium sensitive periodic paralysis nor is it related to that of the long QT syndrome; neverthele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(33 citation statements)
references
References 7 publications
2
31
0
Order By: Relevance
“…Furthermore, our large cohort of ATS1 subjects demonstrated other fundamental ECG and clinical differences between ATS1 and LQTS. In ATS1, patients generally seek medical attention because of periodic paralysis [1][2][3][4]7,8,11 rather than because of the ventricular arrhythmia, consisting of frequent PVCs, mainly in bigeminy, and nonsustained polymorphic, often bidirectional, VT (Tables 1 and 2 and Figure 2), which are usually asymptomatic. Cardiac conduction abnormalities, infrequently seen in LQTS patients, were observed in 23% of ATS1 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our large cohort of ATS1 subjects demonstrated other fundamental ECG and clinical differences between ATS1 and LQTS. In ATS1, patients generally seek medical attention because of periodic paralysis [1][2][3][4]7,8,11 rather than because of the ventricular arrhythmia, consisting of frequent PVCs, mainly in bigeminy, and nonsustained polymorphic, often bidirectional, VT (Tables 1 and 2 and Figure 2), which are usually asymptomatic. Cardiac conduction abnormalities, infrequently seen in LQTS patients, were observed in 23% of ATS1 patients.…”
Section: Discussionmentioning
confidence: 99%
“…The characteristic facial and skeletal abnormalities are often a diagnostic clue to ATS, although they may be subtle. [1][2][3][4] Clinical heterogeneity is remarkable in this syndrome: electrocardiographic (ECG) abnormalities may be the only manifestation of an affected individual within a family with otherwise typical ATS. Recently, ATS has been linked to mutations in the KCNJ2 gene which codes for a voltagegated, inward rectifying potassium channel (Kir2.1).…”
Section: Introductionmentioning
confidence: 99%
“…Andersen-Tawil syndrome (ATS, MIM# 170390) is a rare autosomal dominant disorder characterized by classical triad: (1) ventricular tachyarrythmias associated with QT prolongation in electrocardiograms (ECGs), (2) periodic paralysis, and (3) dysmorphic features (Andersen, et al, 1971;Canun, et al, 1999;Sansone, et al, 1997;Tawil, et al, 1994). Plaster et al revealed that mutations in KCNJ2 (MIM# 600681) caused the syndrome in the majority of clinically diagnosed ATS families (Plaster, et al, 2001).…”
Section: Introductionmentioning
confidence: 99%